2003
DOI: 10.1021/ja0371909
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Quantum Cellular Automata Cells. Electric Field Driven Switching of a Silicon Surface Bound Array of Vertically Oriented Two-Dot Molecular Quantum Cellular Automata

Abstract: The amine functionality of the linker on the dinuclear complex [trans-Ru(dppm)(2)(Ctbd1;CFc)(NCCH(2)CH(2)NH(2))][PF(6)] reacts with Si-Cl bonds of a chlorinated, highly B doped Si (111) surface to yield Si-N surface-complex bonds. The surface bound complex is constrained to a near vertical orientation by the chain length of the linker as confirmed by variable angle XPS. Oxidation of the dinuclear complex with ferrocenium ion or electrochemically generates a stable, biased Fe(III)-Ru(II) mixed-valence complex o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
157
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 208 publications
(158 citation statements)
references
References 45 publications
1
157
0
Order By: Relevance
“…[131] The modification of conducting surfaces at the molecular level with functional active building blocks represents a potential approach to the fabrication of novel types of electrodes. [132] In order to build high quality layers to control the surface properties of electrodes, organic molecules need to be chemically attached. A very interesting approach was proposed in 1992 by Pinson [133] who showed that the reduction of aryl diazonium salt at carbon surfaces resulted in a strongly attached surface layer (electrochemical grafting) and suggested covalent bond formation between an aryl radical and the carbon surface.…”
Section: Surface Functionalization By Electrochemical Reduction Of DImentioning
confidence: 99%
“…[131] The modification of conducting surfaces at the molecular level with functional active building blocks represents a potential approach to the fabrication of novel types of electrodes. [132] In order to build high quality layers to control the surface properties of electrodes, organic molecules need to be chemically attached. A very interesting approach was proposed in 1992 by Pinson [133] who showed that the reduction of aryl diazonium salt at carbon surfaces resulted in a strongly attached surface layer (electrochemical grafting) and suggested covalent bond formation between an aryl radical and the carbon surface.…”
Section: Surface Functionalization By Electrochemical Reduction Of DImentioning
confidence: 99%
“…It inherently diminishes the energy partition between the ground state and the primary energized state which debases the execution of such a device as far as highest working temperature, protection from entropy, and least exchanging time [15]. ii) Multilayer-based wire-crossing strategy utilizes a hybrid crossover technique.…”
Section: Wire Crossing Techniquementioning
confidence: 99%
“…Molecular QCA cells correspond to a class of compounds called mixed-valence compounds, which contain multiple redox centers in different oxidation states. For a molecular QCA device, each "quantum dot" or "charge container" would be a single redox center, and the redox centers would be rigidly held together by covalent bonds [14]. A recent experiment demonstrates that applying reasonable electric fields (like from a clock structure) can move a charge between two sites of a molecule engineered to function as a two-dot QCA cell [14].…”
Section: Devicesmentioning
confidence: 99%
“…For a molecular QCA device, each "quantum dot" or "charge container" would be a single redox center, and the redox centers would be rigidly held together by covalent bonds [14]. A recent experiment demonstrates that applying reasonable electric fields (like from a clock structure) can move a charge between two sites of a molecule engineered to function as a two-dot QCA cell [14]. Thus, experimental results show molecules that act as QCA devices, switching between a chemical representation of a binary 0 and a binary 1.…”
Section: Devicesmentioning
confidence: 99%